Elemen pendukung organizasional Citizenship behavior - Muhammad Umar Data; Susianah Mochtar (AkMen JURNAL ILMIAH, 2021)
This research wants to know that supporting elements that affect organizational citizenship behavior are work motivation, organizational commitment, compensation and job satisfaction. Data were collected through a questionnaire that was sent directly to the sample using accidental sampling technique with a total sample of 60 administrative employees of PT PLN (Persero). The results of the research found that work motivation, organization, compensation and job satisfaction have a significant effect on organizational citizenship behavior